Septic shock in obstetrics: the role of efferent techniques for endotoxin removal in Gram-negative sepsis - A. Zh. Bayalieva; V. R. Davydova (IRBIS LLC, 2024)
Aim: to assess the sorption capacity of various devices for endotoxin removal modelled in in vitro patient with septic shock experiment.Materials and Methods. Endotoxin adsorption was evaluated in vitro by using circulating endotoxin solution in bovine serum in a closed circuit. The following columns were chosen for the experiment: Toraymyxin PMX-20R (РМ Х), Alteco® LPS Adsorber, Efferon LPS, Toray Filtryzer BK-2.1U. Lipopolysaccharide (LPS) doses corresponding to severity of the septic process were sequentially added to a column pre-washed with physiological solution. The first LPS dose of 12.5 µg was added to a flask containing 1500 ml (1.5 L) of fetal bovine serum, a second LPS dose of 37.5 µg was added at 120 minute; the serum samples were collected before the onset of experiment, as well as 30, 60, 120 (before the second dose), 120 (after the second dose), 150 and 240 minutes after the start of circulation. LPS measurement was carried out by mixing the prepared serum sample with LAL reagent at 1:1 ratio in a measuring tube.Results. All columns can reduce endotoxin levels below the 12.5 µg and even 50 µg levels, although none of devices were able to reduce the LPS level from "supercritical" 50 µg to "critical" 12.5 µg. However, at the same time, the capacity of the Toraymyxin PMX-20R column turned out to be 5-13 times greater than that of other products. This result suggests that while removing endotoxin under similar conditions, the Toraymyx in PMX-20R column will have a much higher reserve of sorption capacity and, therefore, greater opportunities for lowering a risk of septic shock progression.Conclusion. The study we presented provides insights into whether sorption capacity of the tested cartridges is sufficient to remove endotoxin at initial (12.5 µg) load that corresponds to the onset of systemic inflammatory response syndrome in a typical patient. Additionally, it elucidates to what extent a cartridge can reduce the endotoxin load in severe septic shock with a total LPS load of up to 50 µg.